Seismic performance of superimposed RC shear walls with concealed bracings using different horizontal connections. (1st July 2022) - Wang, Mengfu; Guo, Shengqi; Jing, Fei; Zhang, Yaqing
Abstract: To enrich the horizontal connection method and to further study the seismic performance of superimposed RC shear walls with concealed bracings (SRCBSWs) using different horizontal connections, three specimens including SRCBSW with horizontal connection by steel plate bolt kit (SPBK), SRCBSW with horizontal connection by U-ring buckle insert (URBI) and cast-in-place shear wall with concealed bracings were tested under quasi-static loading test. Test results indicated that SRCBSWs exhibited the seismic performance close to that of cast-in-place specimen. The horizontal connection of URBI not only enabled achieve the goal of equivalent cast-in-place connection, but had a beneficial effect on the energy consumption. Due to the fact that the steel plates of SPBKs slipped relative to the contact concrete, the horizontal connection by SPBK was not conducive to energy dissipation and stiffness degradation of the wall, while the load-bearing capacity and deformation characteristic could be enhanced due to the cooperative work of steel plates and concrete in later loading. Finite element analysis of SRCBSWs by Abaqus was conducted based on the proposed modelling techniques, and the reasonable accuracy of the numerical method was verified. The parametric analysis results showed that the axial load ratio, volumetric ratio of the X-shaped steel plate bracings and longitudinal reinforcement ratio in hidden column had obvious effect on the load-bearing capacity and elastic stiffness of SRCBSWs. Taking displacement ductility into account, the axial load ratio of SRCBSWs should be reasonably restricted in practice. Moreover, appropriate thickness of steel plates in SPBKs should be determined according to actual demand, but at least one set of SPBK needed to be arranged in the middle of the wall along the height direction when conducting the layout of SPBK. Besides, the inserted reinforcement ratio in URBI could be reinforced in accordance with the constructional requirements. Highlights: ● Two kinds of horizontal connection methods, steel plate bolt kit connection and U-ring buckle insert connection, were proposed in this research. ● Two superimposed RC shear walls with concealed bracings using different horizontal connections were constructed and tested by quasi-static loading test. ● Finite element analysis (FEA) by Abaqus was carried out to further investigate the effect of critical parameters. ● Further explore design recommendations for the structural details at horizontal connection were conducted by FEA.